Clues on void evolution - I. Large-scale galaxy distributions around voids - Ceccarelli, Maria Laura (2013)
We perform a statistical study focused on void environments. We examine galaxy density profiles around voids in the Sloan Digital Sky Survey (SDSS), finding a correlation between void-centric distance to the shell of maximum density and void radius when a maximum in overdensity exists. We analyse voids with and without a surrounding overdense shell in the SDSS. We find that small voids are more frequently surrounded by overdense shells whereas the radial galaxy density profile of large voids tends to rise smoothly towards the mean galaxy density. We analyse the fraction of voids surrounded by overdense shells finding a continuous trend with void radius. The differences between voids with and without an overdense shell around them can be understood in terms of whether the voids are, on average, in the process of collapsing or continuing their expansion, respectively, in agreement with previous theoretical expectations. We use numerical simulations coupled to semi-analytic models of galaxy formation in order to test and interpret our results. The very good agreement between the mock catalogue results and the observations provides additional support to the viability of a λ cold dark matter model to reproduce the large-scale structure of the Universe as defined by the void network, in a way which has not been analysed previously.